How to invest in farmers? A guide for agriculture human capital investment projects - Gammelgaard, Johanna; Franzel, Steven; Du Bois, Rodrigo Salcedo; Kumar, Ashok; Davis, Kristin E.; Preissing, John; Pankowska, Katarzyna (Food and Agricultural Organization of the United Nations, 2023)
Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agrifood systems. A global study carried out by the FAO Investment Centre and the International Food Policy Research Institute (IFPRI), with support from the CGIAR Research Program on Policies, Institutions, and Markets (PIM) and the FAO Research and Extension Unit, looks at agriculture human capital investments, from recent trends to promising initiatives. This toolkit aims to provide investors including policymakers, government officials, international and national development banks and the private sector, with the evidence, analysis, guidance and processes to make sounder investment decisions on projects, programmes and policies that strengthen farmers’ capacities. This publication is part of the Investment Toolkits series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.